Do social protection programs foster short-term and long-term migration adaptation strategies? - Mueller, Valerie; Gray, Clark; Handa, Sudhanshu; Seidenfeld, David (Cambridge University Press, 2020)
We examine how migration is influenced by temperature and precipitation variability, and the extent to which the receipt of a cash transfer affects the use of migration as an adaptation strategy. Climate data is merged with georeferenced panel data (2010–2014) on individual migration collected from the Zambian Child Grant Program (CGP) sites. We use the person-year dataset to identify the direct and heterogeneous causal effects of the CGP on mobility. Having access to cash transfers doubles the rate of male, short-distance moves during cool periods, irrespective of wealth. Receipt of cash transfers (among wealthier households) during extreme heat causes an additional retention of males. Cash transfers positively spur long-distance migration under normal climate conditions in the long term. They also facilitate short-distance responses to climate, but not long-distance responses that might be demanded by future climate change.